2021
DOI: 10.3390/ma14195606
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Durability Properties of Antimony Tailing Coarse Aggregate (ATCA) Concrete

Abstract: Antimony (Sb) is a trace element applied widely in modern industry. A large number of tailing solid wastes are left and accumulated in the mining area after purifying the precious antimony from the antimony ores, causing serious pollution to the environment. The major aim of this study is to investigate the feasibility of utilizing antimony tailing coarse aggregate (ATCA) as a complete substitute for natural coarse aggregate (NCA) in high-strength concrete. Concrete specimens with 25%, 50%, 75%, and 100% ATCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Many scholars have dug down deep into this field. For example, Li et al [30] and Wang et al [24] used antimony tailings as coarse aggregate instead of lifting coarse aggregate in conventional concrete and explored its indices in terms of strength, stability, and toxic leaching aspects. When antimony tailings were used as coarse aggregate, the specimens had better tensile strength and compressive modulus of elasticity than the concrete using a natural rock as coarse aggregate; the cubic compressive strength, splitting tensile strength, and prismatic compressive elastic modulus are 1.31, 2.22, and 1.40 times that of natural rock, respectively, but their alkali activity and cracking sensitivity were less compared to conventional concrete.…”
Section: Using Antimony Tailings To Prepare Raw Materials For Buildin...mentioning
confidence: 99%
“…Many scholars have dug down deep into this field. For example, Li et al [30] and Wang et al [24] used antimony tailings as coarse aggregate instead of lifting coarse aggregate in conventional concrete and explored its indices in terms of strength, stability, and toxic leaching aspects. When antimony tailings were used as coarse aggregate, the specimens had better tensile strength and compressive modulus of elasticity than the concrete using a natural rock as coarse aggregate; the cubic compressive strength, splitting tensile strength, and prismatic compressive elastic modulus are 1.31, 2.22, and 1.40 times that of natural rock, respectively, but their alkali activity and cracking sensitivity were less compared to conventional concrete.…”
Section: Using Antimony Tailings To Prepare Raw Materials For Buildin...mentioning
confidence: 99%
“…Over the past decade or so, the amount of construction waste has been on the rise. Many researchers have conducted numerous studies on the applicability of construction waste in construction projects [1][2][3][4][5][6][7]. RAC is a green concrete that replaces natural concrete aggregates (NCA) with some or all RCA to achieve sustainable building materials.…”
Section: Introductionmentioning
confidence: 99%
“…Copper tailings can refine the pore size and promote long-term strength development of concrete [26], and replacing sand with copper tailings is conducive to the utilization of copper tailings and the improvement of concrete mechanical strength on the premise that the mechanical strength of concrete meets requirements. Li et al [27] prepared ecological concrete using antimony tailings as aggregates, and the results revealed that high-strength concrete at different substitution rates meets the requirements of industry standards. Otieno et al [28] used kimberlite tailings as aggregates in concrete and suggested that the addition of kimberlite tailings reduced the compressive strength and durability of concrete, whereas appropriate mix ratio and admixture could make up for the negative effects of kimberlite tailings.…”
Section: Introductionmentioning
confidence: 99%